A Study and Survey of the Perception towards Makerspaces of the Public Library - Ahn, In‐Ja; Noh, Younghee (International Journal of Knowledge Content Development & Technology, 2018)
In the advent of the fourth industrial revolution, which was to become an innovative society, we now face the forefront of a technological revolution, and in response to these changes, the world is actively developing the maker movement to nurture new innovations. Accordingly, it is necessary to change the functions of the library in order to play a leading role in a changing life environment. In addition, it is necessary to present certain directions in policies in order to help expand the library’s capabilities to utilize a cultural technology. In this study, we have conducted a survey on public library librarians’ perceptions towards makerspaces, and based on this, we have proposed directions and support policies for public library’s makerspaces and a dissemination structure of makerspaces for the public library. URL: http://ijkcdt.net/xml/14410/14410.pdf